2020
DOI: 10.1016/j.seppur.2020.116814
|View full text |Cite
|
Sign up to set email alerts
|

Flue gas purification with membranes based on the polymer of intrinsic microporosity PIM-TMN-Trip

Abstract: Flue gas purification experiments were performed with a membrane made from the ultrapermeable polymer of intrinsic microporosity (PIM) based on tetramethyltetrahydronaphthalene unit coupled with bicyclic triptycene (PIM-TMN-Trip). Permeation experiments with a CO2-N2-O2-SO2 mixture, simulating flue gas from power plants, were performed by means of an in-house developed permeation unit. The results showed very high permeability of the membrane for sulfur dioxide SO2 and high permeability of CO2, lying mainly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…331 PIM-TMN-Trip, another PIM with a triptycene unit in the backbone, did not show obvious CO 2 -induced plasticization effects when exposed to a feed mixture of 22.2 vol% CO 2 , 6.8 vol% O 2 , 70.2 vol% N 2 , and 2220 ppm SO 2 over a trans-membrane pressure difference from 1 to 4 bar. 332 However, as the CO 2 partial pressure was limited to less than 4 bar, plasticization may not have been observed, which would necessitate tests at higher feed pressures, if required for the application.…”
Section: Approaches To Mitigate Plasticizationmentioning
confidence: 99%
“…331 PIM-TMN-Trip, another PIM with a triptycene unit in the backbone, did not show obvious CO 2 -induced plasticization effects when exposed to a feed mixture of 22.2 vol% CO 2 , 6.8 vol% O 2 , 70.2 vol% N 2 , and 2220 ppm SO 2 over a trans-membrane pressure difference from 1 to 4 bar. 332 However, as the CO 2 partial pressure was limited to less than 4 bar, plasticization may not have been observed, which would necessitate tests at higher feed pressures, if required for the application.…”
Section: Approaches To Mitigate Plasticizationmentioning
confidence: 99%
“…Remarkably, the mixed gas performance of PIM‐SBI‐Trip and PIM‐1/SBI‐Trip shows systematically higher selectivities than aged PIM‐TMN‐Trip and with similar CO 2 permeability (Figure S20, Supporting Information), demonstrating the potential of these ultrapermeable PIMs for biogas upgrading [ 32 ] and CO 2 capture from flue gases. [ 34 ] Previous work with benchmark polymer PIM‐1 shows significantly improved selectivity in hollow fiber membranes, [ 35 ] suggesting that also for the present polymers even better separation performance may be expected when prepared in the form of asymmetric or thin film composite membranes.…”
Section: Resultsmentioning
confidence: 85%
“…The objective of the present study was to prove the practical applicability of this new membrane material, not only with model mixtures but also with real, industrially relevant gas streams. Such studies are extremely rare for PIMs with, to our knowledge, only the CO2 capture from a real flue gas stream by PIM-1 [30] or by PIM-TMN-Trip [31], the polymer used in the present study, being reported. Here, the transport and separation properties of PIM-TMN-Trip [21], were studied with both pure gas streams (CH4 and CO2) and mixed gas streams based on either model binary mixtures or on raw biogas.…”
Section: Introductionmentioning
confidence: 98%